2010
DOI: 10.3109/00365540903496544
|View full text |Cite
|
Sign up to set email alerts
|

Burden of respiratory syncytial virus in hospitalized infants and young children in Amman, Jordan

Abstract: Acute respiratory infections (ARI) play a major role in hospitalizations in the Middle East, but the specific viral causes are unknown. We conducted prospective viral surveillance in children <5 y of age admitted with ARI and/or fever at 2 dissimilar hospitals in Amman, Jordan during peak respiratory syncytial virus (RSV) season. We collected prospective clinical and demographic data and obtained nose/throat swabs for testing for RSV by real-time polymerase chain reaction (RT-PCR). We obtained clinical and lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 36 publications
3
34
1
Order By: Relevance
“…RSV showed circulation throughout most of the year but was highly seasonal, with annual peaks between November and February. This finding is consistent with both temperate North America [8] and with previous studies that have identified RSV seasons in Egypt, Jordan, Qatar, Saudi Arabia and the United Arab Emirates within the same time frame [33] and with the highest peak in January [30]. The height of hMPV circulation was between January and May, which is consistent with its pattern of infection in temperate climates, where peaks occur either with or just after RSV in late winter or spring [7].…”
Section: Discussionsupporting
confidence: 92%
“…RSV showed circulation throughout most of the year but was highly seasonal, with annual peaks between November and February. This finding is consistent with both temperate North America [8] and with previous studies that have identified RSV seasons in Egypt, Jordan, Qatar, Saudi Arabia and the United Arab Emirates within the same time frame [33] and with the highest peak in January [30]. The height of hMPV circulation was between January and May, which is consistent with its pattern of infection in temperate climates, where peaks occur either with or just after RSV in late winter or spring [7].…”
Section: Discussionsupporting
confidence: 92%
“…Thirty‐seven studies from 24 countries published between 2002 and 2014, with suitable case fatality data among children <5 years of age with community‐acquired, medically attended, confirmed RSV‐ARI were included in the mortality analysis. The case fatality estimates (reported per 1,000 children) were stratified according to age and region (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Two previous QCMD panels were available for HMPV testing, the 2006 MPV.RSV06 and 2009 MPV.RSVRNA09 (www.qcmd.org) 40, 42 . The 2006 EQA panel comprised cultured A1 and B1 viruses at dilutions from 10 −3 to 10 −7 ; all were detected by the NL-N 2 assay except one sample containing A1 at 2×10 −6 dilution.…”
Section: Resultsmentioning
confidence: 99%